Penerapan Disiplin Kerja dan Tanggung Jawab Pegawai Pada Kantor Kecamatan - Nurdin, Nurul Ainun; Ramadan , Ramadan; Fitriani, Fifi; Hasmi, Hasmi; Dinsar, Arfandy (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
This research aims to determine the application of work discipline and employee responsibilities at the West Bacukiki District Office, Parepare City. The approach method used is a qualitative descriptive type and data collection techniques use observation and interviews. In this research, primary data sources were used in the form of data obtained in the field during interviews and secondary data in the form of data from important documents at the West Bacukiki District Office, Parepare City. The results of the research show that the implementation of work discipline and employee responsibility at the West Bacukiki Parepare District Office is still not good. This can be seen from leaders and employees who do not comply with office operating hours, employees who do not make the best use of their time in carrying out their duties, not targeting their work, and employees' daily work reports that are not carried out.